Long foraging movement of a denning tundra wolf ... - Paquet, P.C.; Hik, D.S.; Frame, P.F.; Cluff, H.D. (University of Alberta Library, 2004)
Wolves (Canis lupus) on the Canadian barrens are intimately linked to migrating herds of barren-ground caribou (Rangifer tarandus). We deployed a Global Positioning System (GPS) radio collar on an adult female wolf to record her movements in response to changing caribou densities near her den during summer. This wolf and two other females were observed nursing a group of 11 pups. She traveled a minimum of 341 km during a 14-day excursion. The straight-line distance from the den to the farthest location was 103 km, and the overall minimum rate of travel was 3.1 km/h. The distance between the wolf and the radio-collared caribou decreased from 242 km one week before the excursion to 8 km four days into the excursion. We discuss several possible explanations for the long foraging bout. ...